Pre-school mental health disorders: a review. (2nd April 2020) - Zaim, Nadia; Harrison, Joyce
Abstract: Preschoolers are presenting in increasing numbers to primary care providers and mental health clinics with emotional and behavioural impairment. Preschoolers in the US have the highest rates of school expulsion of all age groups. Because young children are limited in their capacity to convey distress and internal states, impairment is most often expressed behaviourally. Disruptive behaviour, frequently in the form of aggression or dysregulation, is a final common pathway for many disorders in this age group. Tools and training to diagnose pre-school disorders are limited, and while some effective non-medication interventions exist, the evidence base for medication use in this age group is extremely limited. This article reviews approaches to assessing common pre-school disorders including attention deficit hyperactivity disorder (ADHD), disruptive behaviour disorders, anxiety and mood disorders, perceptual disturbances and psychosis, and trauma related disorders. The evidence base for both therapeutic and psychopharmacologic interventions for these disorders is discussed.